A identidade e a imagem organizacional do Mercado Municipal Antônio Franco em Aracaju – SE : uma análise a partir da visão dos stakeholders - Araujo, Marcus Vinícius Oliveira (2020)
This study was about the organizational universe that involves the Antônio Franco municipal market considering historical and cultural aspects, operationalized by the theories of organizational identity and organizational image. The present research had the general objective of understanding the elements that constitute the identity and the organizational image of the Municipal Market Antônio Franco de Aracaju / SE from the perspective of internal and external stakeholders. With regard to specific objectives, they are as follows: Identify the historical element in the construction of the organizational identity of the municipal market Antônio Franco; Detect the mission and values, as well as the central characteristics that differentiate the Antônio Franco municipal market from other organizations; Identify the individual and collective practices of handicraft traders in the Antônio Franco municipal market in the search for economic and cultural development; Understand how the formation of the imaginary occurs in relation to the tourist activity present in the municipal market Antônio Franco and Investigate the process of building the organizational image in the municipal market Antônio Franco in the view of external stakeholders. With regard to the methodology, the study is classified as exploratory and descriptive, with a qualitative approach, which aims to understand the phenomenon studied through the research method of single case study. The data collection included 28 interviews, among which 10 were traders, 16 tourists and 2 guides who provided theoretical saturation. Participant observation was applied in two stores in order to identify the behavior, the conduct of their business and the relationship of merchants with each other and in customer service. The data were analyzed using the content analysis technique. The survey also considered the analysis of secondary documents available in libraries, bookstores and websites. It was concluded that the identity of the Antônio Franco municipal market is dynamic and flexible, being considered from four different moments: Being a beautiful and grand portico from its inauguration in 1926 until 1950, a concentrated and disorganized anthill from 1950 until the restructuring between the years 1926 to 1998, an emotional disappointment during the transition period between 1998 and 1999 and like the sunrise after the 2000s with the delivery of a renovated development. Currently, the organization's identity is made up of cultural diversity, traditions, handicrafts and the representation of the city of Aracaju. The main values are authenticity with the culture of Sergipe and the Northeast, in addition to the preservation of history and culture. The image of the Antônio Franco municipal market is understood by external stakeholders and disseminated by internal stakeholders as a shopping environment that transmits the culture of the Northeast, being also noted as a material and immaterial cultural heritage of the city of Aracaju.